Zastosowanie nowych barwników w chirurgii okulistycznej - Rejdak, Robert; Oleszczuk, Agnieszka; Mańkowska, Anna; Kiczyńska, Magdalena; Zagórski, Zbigniew; Żarnowski, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
The aim of this paper is to present recent developments in the area of novelty of vital dyes in intraocular surgery. The authors present the advantages and disadvantages of several vital dyes currently used in ophthalmic surgery. Vital dyes are used to allow better intraoperative visualization of both the anterior and posterior segments. Indocyanine green and trypan blue are the most frequently used and the most efficacious dyes for staining the important anatomic areas but often are associated with significant side effects. These dyes are used in cataract and vitreo-retinal surgery. Other dyes including rhodamine 6G, E68, bromophenol blue, light green and Chicago blue are still under preclinical assessment.